Reinforcement of economical and environment friendly Acacia catechu particles for the reduction of brittleness and curing temperature of polybenzoxazine thermosets. (February 2018) - Dayo, Abdul Qadeer; Ma, Rui-kun; Kiran, Sadia; Zegaoui, Abdeldjalil; Cai, Wan-an; Shah, Ahmer Hussain; Wang, Jun; Derradji, Mehdi; Liu, Wen-bin
Abstract: The brittleness always remained a major concern for the polybenzoxazine thermosets. Several attempts have been made to overcome the brittleness issue, but all find some kind of sacrificing in other properties. A new and economical approach is presented by the reinforcement of catechin-rich Acacia catechu (AC) particles. The micro size AC particles blended with bisphenol-A aniline-based benzoxazine (BA-a) resin and isothermally cured. The terminal OH groups of produced tannic acid participated in the curing process and helped in the ring opening of BA-a resin. The composites exhibited that the brittleness of polybenzoxazine has been improved by 35%, simultaneously its strength, Youngs' modulus, stiffness, glass transition temperature, and thermal stabilities are also enhanced. The highest impact strength of the composite is observed on only 4 wt% loading of AC particles and read as 5.2 ± 0.16 kJ/m 2, 307.1% higher than the value of neat poly(BA-a).